The Impact of Screw Density on the Outcomes of Adolescent Idiopathic Scoliosis Correction Surgery: A Multicenter Retrospective Study - ZhaoJun Lu; Chong Liu; JiaKun Li; XiaoPeng Qin; Jiarui Chen; Jiang Xue; Hao Li; Tianyou Chen; Tao Chen; XinLi Zhan (Journal of Investigative Surgery)
Background To evaluate the efficacy of low screw density constructs versus high screw density constructs in adolescent idiopathic scoliosis (AIS) surgery.Methods Data were collected from AIS patients who underwent pedicle screw fixation surgery at two medical centers. Patients were stratified into low and high screw density groups, calculated as pedicle screws per fused vertebral level. The dataset comprised demographics, radiological parameters, surgical outcomes and postoperative complications.Results Of 213 AIS patients analyzed, 114 and 99 comprised low- and high-density groups respectively. Compared with high-density constructs, low-density constructs demonstrated shorter operative time (median: 17.93 min, IQR: 14.66–20.50 vs. 22.15 min, IQR: 16.80–24.77; p = 6.30e−07), lower intraoperative blood loss (median: 762.29 ml, IQR: 600–900 vs. 954.19 ml, IQR: 800–1030; p = 7.70e−07), fewer postoperative pain (median: 4.719, IQR: 3–7 vs. 5.505, IQR: 3.5–7; p = 0.009), and shorter hospital stays (median: 11.15 days, IQR: 7–13.5 vs. 12.48 days, IQR: 8–15; p = 0.04). Both groups had equivalent Cobb angle correction (median: 67.31%, IQR: 60.50% –76.84% vs. 67.97%, IQR: 62.54%–73.52%; p = 0.90).Conclusion Optimizing screw density may minimize intraoperative blood loss and postoperative pain without affecting correction efficacy in AIS; however, longitudinal studies are needed to assess long-term functional and quality-of-life outcomes.